2022
DOI: 10.1111/hiv.13376
|View full text |Cite
|
Sign up to set email alerts
|

Bictegravir/emtricitabine/tenofovir alafenamide in patients with genotypic NRTI resistance

Abstract: Background: Bictegravir/emtricitabine/tenofovir alafenamide (B/F/TAF) is approved for treatment of HIV without known resistance to its components.Several studies have demonstrated efficacy of B/F/TAF in patients with nucleoside reverse transcriptase inhibitor (NRTI) resistance-associated mutations (RAMs), mainly identified by proviral DNA testing, but data on the efficacy of B/F/TAF in patients with NRTI RAMs identified in viraemic plasma are limited.Methods: We used a retrospective analysis of patients receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…A previous pooled analysis of the BICSTaR study suggested that people who have neuropsychiatric symptoms when starting treatment were less likely to have an undetectable viral load at 12 months [33]. Overall, our current findings add to the data supporting B/F/TAF as an effective option for a broad range of people, including those with late HIV diagnosis [27], women [34], older individuals [15,28,34,35], people of black race [36], and those with evidence of pre-existing viral resistance (mainly M184V/I) [30,37]. CD4 cell count and CD4/CD8 ratio were statistically significantly improved in TN participants and, to a lesser extent, in TE participants, consistent with the known benefits of ART [4,11,18,20], indicating a shift towards restoration of immunological function.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…A previous pooled analysis of the BICSTaR study suggested that people who have neuropsychiatric symptoms when starting treatment were less likely to have an undetectable viral load at 12 months [33]. Overall, our current findings add to the data supporting B/F/TAF as an effective option for a broad range of people, including those with late HIV diagnosis [27], women [34], older individuals [15,28,34,35], people of black race [36], and those with evidence of pre-existing viral resistance (mainly M184V/I) [30,37]. CD4 cell count and CD4/CD8 ratio were statistically significantly improved in TN participants and, to a lesser extent, in TE participants, consistent with the known benefits of ART [4,11,18,20], indicating a shift towards restoration of immunological function.…”
Section: Discussionsupporting
confidence: 55%
“…A previous pooled analysis of the BICSTaR study suggested that people who have neuropsychiatric symptoms when starting treatment were less likely to have an undetectable viral load at 12 months [33]. Overall, our current findings add to the data supporting B/F/TAF as an effective option for a broad range of people, including those with late HIV diagnosis [27], women [34], older individuals [15, 28, 34, 35], people of black race [36], and those with evidence of pre‐existing viral resistance (mainly M184V/I) [30, 37].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…[3,8,[19][20][21] Several small real-world evidence (RWE) studies have shown the effectiveness and safety of B/F/TAF in routine clinical practice. [22][23][24][25][26][27][28][29][30][31][32] However, there is little RWE with B/F/TAF in the Canadian population. The only available evidence from Canada comes from specific population groups, such as TN migrant people in a Montreal-based multidisciplinary HIV care clinic receiving rapid cost-covered B/F/TAF initiation, [31,32] and a retrospective chart review in people with previously documented primary nucleoside reverse transcriptase inhibitor (NRTI) resistance at a single center in Alberta.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our case, if a PWH presents with MPV, has baseline HIV VL suppression and full ARV regimen activity (no significant nucleoside/tide reverse transcriptase inhibitor [NRTI] mutations), 11,12 or is treatment-naïve, then these authors recommend no bictegravir adjustment or alternative treatment strategy. If significant baseline NRTI resistance exists and/or a prolonged tecovirimat regimen is prescribed, then an empiric ARV switch (dolutegravir [metabolism primarily via UDG, no expected tecovirimat interaction] substitution) may be necessary to avoid a DDI with potential VL compromise for 14 days after the completed MPV treatment.…”
mentioning
confidence: 99%